Implementasi Kurikulum Industri Dengan Pendekatan Competency-Based Training Pada Desain Komunikasi Visual - Permatasari, Karina; Tinus, Agus; Wurianto, Arif Budi (Akademi Komunitas Negeri Aceh Barat, 2025)
AbstractThe rapid development of technology and the needs of the creative industry require the alignment of vocational school curriculum, specifically in visual communication design, with the demands of the job market. This study aims to analyze the planning, implementation, and challenges of industry-based curriculum using a competency-based training approach in producing competent graduates. This is a qualitative descriptive study using a case study design, with data sources including semi-structured in-depth interviews, participatory observation, and document analysis as data collection techniques. Data analysis techniques include the miles and huberman model, triangulation of sources, and methods for testing data validity. The research subjects consisted of three individuals: the curriculum vice principal, the program head, and the visual communication design teacher, with the school principal serving as the key informant. The research findings implementing an industry-based curriculum using a competency-based training approach involves synchronisation between the school and industry to formulate learning outcomes in the fields of content creation, reprographics, and branding. Learning is conducted using the project-based learning method integrated with field work practice and skill evaluation through competency-based skills testing in collaboration with industry. This implementation successfully enhances students' 21st-century competencies such as collaboration, communication, critical thinking, and creativity. This study emphasizes the importance of improving facilities, teacher training, and collaboration with industry to produce competent and adaptive graduates.Keywords:Competency-based training; Visual communication design; Industry curriculum; Student competency AbstrakPerkembangan teknologi dan kebutuhan industri kreatif yang pesat menuntut penyelarasan kurikulum SMK, khususnya di bidang desain komunikasi visual dengan kebutuhan pasar kerja. Penelitian ini bertujuan untuk menganalisis perencanaan, pelaksanaan, dan tantangan kurikulum berbasis industri dengan pendekatan competency-based training dalam menghasilkan lulusan yang kompeten. Jenis penelitian ini adalah kualitatif deskriptif dengan rancangan penelitian menggunakan metode studi kasus (case study), sumber data menggunakan wawancara mendalam semi-terstruktur, observasi partisipatif, dan studi dokumen sebagai teknik pengumpulan data. Teknik analisis data menggunakan miles and huberman model dan triangulasi sumber serta teknik untuk uji keabsahan data. Subjek penelitian terdiri dari 3 orang, yaitu waka kurikulum, kepala program, dan guru pengajar desain komunikasi visual serta kepala sekolah menjadi informan kunci. Hasil penelitian menunjukkan bahwa implementasi kurikulum berbasis industri dengan pendekatan competency-based training ini melibatkan sinkronisasi antara sekolah dan industri untuk merumuskan capaian pembelajaran pada bidang content creator, reprographics, dan branding. Pembelajaran dilakukan dengan metode project-based learning yang terintegrasi dengan praktik kerja lapangan dan evaluasi keterampilan melalui uji kompetensi keahlian bersama industri. Implementasi ini berhasil meningkatkan kompetensi abad ke-21 siswa seperti kolaborasi, komunikasi, berpikir kritis, dan kreativitas. Penelitian ini menekankan pentingnya peningkatan fasilitas, pelatihan guru, dan kolaborasi dengan industri untuk menghasilkan lulusan yang kompeten dan adaptif.Kata Kunci:Competency-based training; Desain komunikasi visual; Kurikulum industri; Kompetensi siswa